Extraction, and Antibacterial activities of Teucrium polium (Algeada) growing in Iraq (Journal of the College of Basic Education, 2022)
This study was designed to isolate the most important bioactive compounds from the Iraqi plant Teucrium polium using a liquid-liquid extraction method, detected on thin layer chromatography (TLC) plates, and examine the antimicrobial activities Teucrium polium extracts against five bacterial species by using disc-diffusion method. The extracts were identified via Thin Layer Chromatography (TLC) using a mixture of ethyl acetate : methanol : water (100 : 15 : 10). as chromatographic eluent .